Poultry Preslaughter Operations in Hot Environments: The Present Knowledge and the Next Steps Forward - Vieira, Frederico Márcio Corrêa; Portugal, Miguel Angel Guillen; de Borba, Leonardo Piffer; Angrecka, Sabina; Herbut, Piotr; Jongbo, Ayoola Olawole; De-Sousa, Karolini Tenffen; Deniz, Matheus [UNESP] (MDPI, 2024)
Poultry production faces significant challenges, including high feed prices, diseases, and thermal stress, which impact broiler welfare and productivity. Despite advances in cooling technologies and ventilation, preslaughter operations still lead to considerable losses. This review highlights the need for the improved management of thermal environments and animal logistics. Preslaughter operations typically involve fasting broilers for 8–12 h to reduce gastrointestinal contents and contamination. Following fasting, broilers are caught, crated, and transported. Stress levels vary based on distance and conditions, with manual catching often causing stress and injuries. Catching should occur during cooler periods to minimise these issues, and transport conditions must be carefully managed. Lairage, the waiting period after transport, should be kept short (1–2 h) in climate-controlled environments to avoid stress and deterioration. Proper handling and efficient unloading are essential to prevent injuries and reduce economic losses. Stunning methods, such as electronarcosis and a controlled atmosphere, aim to minimise suffering before slaughter, though practices vary culturally and religiously. Logistics and real-time monitoring technology are crucial for enhancing animal welfare during transportation. Effective planning and the optimisation of transport processes is vital for reducing stress and losses, especially with regard to rising global temperatures and production demands.
Keywords: animal welfare; broiler; food safety; logistics; preslaughter operations